2017
DOI: 10.1016/j.biomaterials.2017.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages with cellular backpacks for targeted drug delivery to the brain

Abstract: Most potent therapeutics are unable to cross the blood-brain barrier following systemic administration, which necessitates the development of unconventional, clinically applicable drug delivery systems. With the given challenges, biologically active vehicles are crucial to accomplishing this task. We now report a new method for drug delivery that utilizes living cells as vehicles for drug carriage across the blood brain barrier. Cellular backpacks, 7–10 µm diameter polymer patches of a few hundred nanometers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
99
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(99 citation statements)
references
References 55 publications
0
99
0
Order By: Relevance
“…In 2015, Mitragotri and co‐workers advanced their earlier work by showing that monocytes can deliver backpacks to inflamed areas in the body as a step toward immunotherapeutic applications (see Figure f for more recent iterations of backpacks made from PLGA) . Batrakova and co‐workers later showed that catalase‐loaded backpacks bound to monocytes can penetrate the blood–brain barrier of mice with LPS‐induced encephalitis and reduce inflammation caused by ROS from M1 polarized microglia . Instead of using monocytes and macrophages, Irvine and co‐workers published a study in 2012 using a nanoparticle functionalized with maleimide to bind to T cells for cargo delivery to their synapses as a way to prevent autoimmunity, or conversely, to boost antitumor immunity .…”
Section: Microscale Materials For Immunotherapymentioning
confidence: 99%
“…In 2015, Mitragotri and co‐workers advanced their earlier work by showing that monocytes can deliver backpacks to inflamed areas in the body as a step toward immunotherapeutic applications (see Figure f for more recent iterations of backpacks made from PLGA) . Batrakova and co‐workers later showed that catalase‐loaded backpacks bound to monocytes can penetrate the blood–brain barrier of mice with LPS‐induced encephalitis and reduce inflammation caused by ROS from M1 polarized microglia . Instead of using monocytes and macrophages, Irvine and co‐workers published a study in 2012 using a nanoparticle functionalized with maleimide to bind to T cells for cargo delivery to their synapses as a way to prevent autoimmunity, or conversely, to boost antitumor immunity .…”
Section: Microscale Materials For Immunotherapymentioning
confidence: 99%
“…Wang et al, 2015). PD patients have reduced catalase activity in the substantia nigra (Ambani, Van Woert, & Murphy, 1975), and catalase containing nanoparticle delivery to brain has been explored as a therapeutic strategy in PD animal models (Klyachko et al, 2017).…”
mentioning
confidence: 99%
“…There are several sources from which primary macrophages can be isolated from mice. We selected BMDMs for several reasons, including i) their reported use as drug carriers in other studies, and ii) their higher cell isolation yield and superior capacity for phagocytosis in comparison to macrophages isolated from the spleen or peritoneal cavity . Unfortunately, macrophages were unable to efficiently phagocytose these particles within 24 h, as determined by fluorescence microscopy ( Figure 3A).…”
Section: Resultsmentioning
confidence: 99%